On the CVD Growth of C Nanotubes Over Fe-Loaded Montmorillonite Catalysts - Saveria Santangelo; Elpida Piperopoulos; Maurizio Lanza; Giuliana Faggio; Giacomo Messina; Candida Milone (Nanomaterials and Nanotechnology)
The synthesis of carbon nanotubes (CNTs) by chemical vapor deposition (CVD) of isobutane (i-C4H10) over sodium-exchanged K10-montmorillonite based iron-catalysts is investigated. By studying the influence of iron-addition (5–25 wt%) on the catalyst performances, at 700°C, an empirical relationship is derived relating the mass of CNTs synthesized with the exposed surface of loaded iron, as resulting from simultaneous change of number, size and dispersion of Fe-nanoparticles available for the growth.